Better resilience of wheat KRL 210: A boom for salt-affected ecologies - Sheoran, Parvender; Kumar, Arvind; Sharma, Raman; Singh, Mansukh; Parjapat, Kailash; Singh, Ranjay K; Sharma, P C; Chahal, V P (Indian Farming, 2021)
Properly managing the crops and getting desirable yields in salt-affected ecologies is often achallenging task for the growers. When underground water is of poor (alkali) quality and theclimate is too variable, the compounding vulnerability becomes devastating especially for theresource-limited small landholding farmers. To cope up such stressful conditions, salt tolerantwheat variety ‘KRL 210’, having better resilience and adaptive capacity in degraded farmsituations showed tremendous potential in countering the yield reduction and harnessing thepotential of high RSC water irrigated sodic soils. Emerging successful adoption of such appropriatetechnology can make a real change in transforming the business-as-usual farming into anecologically sustainable and profitable venture.